Assessment of the attractiveness of robotic-assisted radical prostatectomy in the hospitals in Milan. (30th September 2020) - Greco, M; Mosillo, M; Papa, M T; Zanardi, S; Tinaglia, V; Nicolosi, D
Abstract: Background: Robotic-Assisted Radical Prostatectomy (RARP) performed in the hospitals of the Health Protection Agency (ATS) of Milan increased from 302 in 2011 to 1275 in 2019. On the contrary, Traditional Radical Prostatectomy (TRP) remained essentially unchanged (919 hospitalization in 2011, 937 in 2019). The increase in RARP occurred both for Lombardy (L) (223, 7%) and particularly for out-of-Lombardy residents (EL) (565, 5%). In 2011 66.5% of all EL treated with Radical Prostatectomy (RP) (RARP + TRP) in the ATS area were enrolled in hospitals equipped with robots, while in 2019 this percentage rose to 97.5%. In view of this important increase and considering the high density of hospitals with robots in Milan, it was analyzed if the reason for the EL displacement could be due to the possibility of performing a RARP. Methods: The Hospital Discharge Cards (SDO) database was used for the analysis. Admissions to be considered were identified through the main diagnosis of localized malignant prostatic cancer and the surgical intervention of RP. The other urological interventions were identified through the discharge ward. The "residency" field allowed to separate L from EL. Results: Considering the four hospitals where robot technology was already available in 2011, the percentage changes in hospitalizations were compared for: only RP interventions, all urological interventions excluding RP, total hospital production distinguishing between L and EL. RP increased by about 5 percentage points in EL (from 43.5% in 2011 to 48.7% in 2019). For other urological surgeries excluding RP, the increase was about 11 pp (from 16.1% in 2011 to 27.3% in 2019), as well as for general procedures (15.5% in 2011, 26, 2% in 2019). Conclusions: The increase in EL for RP is lower than the increase observed for other urological surgeries and on all hospital production. It can be concluded that it is not the RARP technique itself that is attractive to EL, but rather the reputation of the hospital. Key messages: In 2019 the number of robotic-assisted radical prostatectomy increased 4, 2 times compared to 2011. R-assisted radical prostatectomy is not a determining factor for health mobility towards Lombardy.